1987
DOI: 10.1128/aem.53.10.2271-2274.1987
|View full text |Cite
|
Sign up to set email alerts
|

Production of staphylococcal enterotoxin in mixed cultures

Abstract: Two Staphylococcus aureus strains were grown in brain-heart infusion (BHI) broth and a meat medium with Bacillus cereus, Streptococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa. Both S. aureus strains grew well and produced enterotoxin in the presence of S. faecalis in BHI broth; however, enterotoxin production was observable in the meat medium only when the S. aureus inoculum was greater than the S. faecalis inoculum. S. aureus FRI-100 grown with B. cereus produced enterotoxin in both media only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…aureus counts exceeding 7 log cfu g −1 (Tatini et al 1971(Tatini et al , 1973Van Schouwenburg et al 1979); in some cheeses, enterotoxin production may even occur at 6·80 log cfu g −1 (Tatini et al 1973). Despite the high levels of staphylococci found in this study, no enterotoxins were detected in Batch R. This may have been due to the microflora present as this Batch was elaborated with raw milk (Noleto et al 1987).…”
Section: ------------------------------------------------------------mentioning
confidence: 53%
“…aureus counts exceeding 7 log cfu g −1 (Tatini et al 1971(Tatini et al , 1973Van Schouwenburg et al 1979); in some cheeses, enterotoxin production may even occur at 6·80 log cfu g −1 (Tatini et al 1973). Despite the high levels of staphylococci found in this study, no enterotoxins were detected in Batch R. This may have been due to the microflora present as this Batch was elaborated with raw milk (Noleto et al 1987).…”
Section: ------------------------------------------------------------mentioning
confidence: 53%
“…Other researchers had reported estimated levels of SEA in contaminated chocolate milk and canned mushrooms ranging from 0.4 to 79 ng/g (Evenson et al, 1988, Anderson, 1996. The rapid production of SE under the conditions studied may be due to the lack of competing microflora (Noleto et al, 1987). The blanching treatments essentially eliminated the background microflora to < 10 CFU/g (data not shown).…”
Section: Foodmentioning
confidence: 76%
“…Following sixth hour storage, storage in the refrigerator had a significantly lower S. aureus count than in the room storage (P < 0.01, P < 0.001). The growth of S. aureus in foods is affected by various factors that influence the potential risk such as pH, the initial level of S. aureus, storage conditions, salt amount, moisture and competitive flora (Noleto et al, 1987;Samelis & Metaxopoulos, 1998;Sagun et al, 2003). This study indicated that S. aureus count did not increase in the refrigerator storage because of temperature.…”
Section: Resultsmentioning
confidence: 99%